THIOLS IN HYDROTHERMAL SOLUTION: STANDARD PARTIAL MOLAL PROPERTIES AND THEIR ROLE IN THE ORGANIC GEOCHEMISTRY OF HYDROTHERMAL ENVIRONMENTS - Schulte M.D.; Rogers K.L. (My University, 2004)
In order to assess the potential role of organic sulfur compounds in hydrothermal systems, we use recent advances in theoretical geochemistry to estimate the standard partial molal thermodynamic properties and parameters for the revised Helgeson-Kirkham-Flowers equation of state for aqueous straight-chain alkyl thiols. Thermodynamic properties are used to determine the potential for thiol formation in both modern and Archean hydrothermal systems. We conclude that organic sulfur compounds may hold the key to the organic chemistry that led to the origin of life in hydrothermal settings. These results may also explain the presence of sulfur in a number of biomolecules present in ancient thermophilic microorganisms.